The Personal and Subject-Matter Scope of Arbitration Agreements: A Comparative Study - Sattar Jabar Kazem, Lect. Zainab (Basra studies journal, 2026)
Arbitration is an effective alternative dispute resolution mechanism, particularly in commercial and investment fields, where speed and flexibility are required in resolving disputes outside the framework of lengthy traditional court procedures. The arbitration agreement constitutes the cornerstone upon which the authority of the arbitral tribunal to adjudicate disputes is based, as it reflects the parties’ intention to resort to arbitration instead of national courts. The effectiveness of arbitration largely depends on the clarity of its subject-matter scope, namely the determination of the types of disputes covered by the arbitration agreement, whether arising from a specific contract or future and unspecified disputes. Furthermore, the arbitration agreement is binding upon its parties and, as a contractual clause, is governed by the principle of relativity of contractual effects. Accordingly, the rights and obligations arising under this agreement apply only to its parties and do not extend to third parties, except in exceptional cases recognized by law as deviations from the general rule.